2015
DOI: 10.1016/j.chroma.2015.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Selective capture of glycoproteins using lectin-modified nanoporous gold monolith

Abstract: The surface of nanoporous gold (np-Au) monoliths was modified via a flow method with the lectin Concanavalin A (Con A) to develop a substrate for separation and extraction of glycoproteins. Self-assembled monolayers (SAMs) of lipoic acid (LA) on the np-Au monoliths were prepared followed by activation of the terminal carboxyl groups to create amine reactive esters that were utilized in the immobilization of Con A. Thermogravimetric analysis (TGA) was used to determine the surface coverages of LA and Con A on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Taking into account this fact, the benefits with monoliths are more pronounced in enrichment of glycoproteins because they are usually high molecular weight proteins. Individual lectins or multiple lectins, were bound on different organic‐based monoliths since they offer a variety of chemistries suitable for immobilization . The limited sample capacity was a consequence of the relatively low surface area of organic‐based monoliths .…”
Section: Monoliths For High‐throughput Protein Purification or Screeningmentioning
confidence: 99%
“…Taking into account this fact, the benefits with monoliths are more pronounced in enrichment of glycoproteins because they are usually high molecular weight proteins. Individual lectins or multiple lectins, were bound on different organic‐based monoliths since they offer a variety of chemistries suitable for immobilization . The limited sample capacity was a consequence of the relatively low surface area of organic‐based monoliths .…”
Section: Monoliths For High‐throughput Protein Purification or Screeningmentioning
confidence: 99%
“…The use of SAMs with specific terminal functional groups is important, such as when these groups are activated and coupled to biomolecules for use in development of biosensors [18–20]. In a previous study using thermogravimetric analysis (TGA), we found that the coverage of an alkanethiol SAM within an np-Au monolith was close to that expected on the basis of packing geometry on flat Au [21, 22]. One recent study concerning electrochemical impedance spectroscopy (EIS) studies of alkanethiol SAMs on np-Au from octanethiol to tetradecanethiol (C8, C10, C12, and C14 chain lengths) reported that the charge transfer resistance varied gradually with chain length on np-Au but showed a steadier increase with chain length on flat gold [23].…”
Section: Introductionmentioning
confidence: 96%
“…Accessibility of electrolyte solutions to the interior of np-Au can be viewed as significant for the efficiency of immobilization of biomolecules such as antibodies [3133] or oligonucleotides [25, 34], sensor response [1], loading for controlled release [10, 35], and substrate access and overall activity for immobilized enzymes [36]. Carbohydrate modified np-Au has been recently explored for applications in capture and elution of lectins [21], glycoprotein modified np-Au for competitive electrochemical immunoassay, and lectin-modified np-Au for capture and subsequent elution of glycoproteins [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Owing to its catalytic properties, tunable morphology, microfabrication compatibility and excellent thiol-gold chemistry, np-Au is an emerging material for biosensing applications [20][21][22] . We recently demonstrated that np-Au electrochemical sensors exhibit excellent biofouling-resilience in the presence of complex media such as serum while preserving the sensitive DNA detection capabilities 23,24 .…”
Section: Introductionmentioning
confidence: 99%